Highly Efficient Non-Enzymatic Glucose Sensor Based on CuO Modified Vertically-Grown ZnO Nanorods on Electrode - Rafiq Ahmad (Nature Portfolio, 2017)
Abstract There is a major challenge to attach nanostructures on to the electrode surface while retaining their engineered morphology, high surface area, physiochemical features for promising sensing applications. In this study, we have grown vertically-aligned ZnO nanorods (NRs) on fluorine doped tin oxide (FTO) electrodes and decorated with CuO to achieve high-performance non-enzymatic glucose sensor. This unique CuO-ZnO NRs hybrid provides large surface area and an easy substrate penetrable structure facilitating enhanced electrochemical features towards glucose oxidation. As a result, fabricated electrodes exhibit high sensitivity (2961.7 μA mM−1 cm−2), linear range up to 8.45 mM, low limit of detection (0.40 μM), and short response time (<2 s), along with excellent reproducibility, repeatability, stability, selectivity, and applicability for glucose detection in human serum samples. Circumventing, the outstanding performance originating from CuO modified ZnO NRs acts as an efficient electrocatalyst for glucose detection and as well, provides new prospects to biomolecules detecting device fabrication.